Analisis Alur Marketing Mix di Industri Batik Kampoeng Batik Laweyan - Azizah, Annisa' Fitri, Siti Nandiroh, S.T, M.Eng, Ida Nursanti, S.T., M.Eng.Sc (2015)
Batik industry is a prayer one factor supporting the Indonesian Economy. In Central Java are batik center industry, in Laweyan, Surakarta. The Laweyan have small batik industry, intermediate, and big using batik technique, hats and printing. Kampoeng Batik Laweyan originally the individual efforts manufacturers simultaneously seller batik in Laweyan then set Forum Pengembangan Kampoeng Batik Laweyan (FPKBL). That is the purpose of research husband provide data updates FPKBL in batik industry, knowing the distribution of batik product distribution, and application of the marketing mix marketing hearts. Benefits research husband that can be used as information and input subscription with distribution and marketing batik, also as references further research. Currently FPKBL batik have business houses 73 units, of which 30 are producing batik batik industry with produce batik, cap, and printing. Of the 30 industry batik, there are 12 batik industry as respondents willing hearts research. Methods of data collection by observation, questionnaires, interviews, and documentation. The research method used namely marketing mix and descriptive statistics in on results production and distribution. Distribution and marketing is a unitary system of overall business activity. Product distribution batik hearts illustrated chart that has form accompanied with descriptive statistical analysis. Furthermore, product marketing merketing approach described with mix (product, place, promotion, price, physical environments, processes, and people). The result that is obtained commercially to sell industrial products batik form of batik cloth, clothing, accessories, batik painting, and needs household. Marketing mix has been applied with good posted batik industry as hearts marketing approach. Keywords: Batik, Distribution and Marketing, Production, Marketing Mix, Descriptive Statistics